Anode for fluoride ion battery and fluoride ion battery

By using metal fluoride as the negative electrode live material in fluoride ion batteries, and combining specific battery collector materials and structures, the problem of irreversible battery reaction caused by the conductive auxiliary materials of carbon materials in the prior art is solved, and a more efficient fluoride ion battery performance is achieved.

JP7669004B2Active Publication Date: 2025-04-28NISSAN MOTOR CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021070390
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-21
Filing Date
2021-04-19
Publication Date
2025-04-28
Estimated Expiration
2041-04-19

AI Technical Summary

Technical Problem

In the prior art, when the negative electrode living material AlF3 and the conductive auxiliary material of the fluoride ion battery are carbon materials, it is difficult to achieve a reversible battery reaction.

Method used

Metal fluoride is used as the negative electrode active material, and a specific surface film is formed on the negative electrode battery collector to ensure that the defluoride potential of the metal fluoride is lower than the reduction and decomposition potential of the film. At the same time, aluminum or magnesium or its alloy is used as the negative electrode battery collector material, and carbon material is not included as the conductive auxiliary material.

Benefits of technology

It effectively promotes the reversible battery reaction of fluoride ion batteries, and suppresses the reduction and decomposition reaction of the electrolyte, thereby improving the charging and discharging characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669004000008
    Figure 0007669004000008
  • Figure 0007669004000009
    Figure 0007669004000009
  • Figure 0007669004000010
    Figure 0007669004000010
Patent Text Reader

Abstract

To provide means capable of sufficiently proceeding reversible battery reaction in a fluoride ion battery.SOLUTION: In a negative electrode for a fluoride ion battery having a negative electrode active material layer containing a negative electrode active material and a negative electrode current collector for collecting a current of the negative electrode active material layer, the negative electrode active material contains metal fluoride whose defluorination reaction potential is nobler than the reduction decomposition potential of an inert coating composed of oxides and fluorides formed on the surface of the negative electrode current collector; a constituent material of the negative electrode current collector is aluminum or magnesium or an alloy thereof; and the negative electrode active material layer does not contain a conductive auxiliary agent made of a carbon material.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode for a fluoride ion battery and a fluoride ion battery. [Background technology]

[0002] Lithium-ion batteries (LIBs) are known as high-voltage and high-energy-density storage batteries. LIBs are made up of Li ions embedded in the positive and negative electrode host crystals. + This is a cation-based battery that utilizes the reversible insertion and deinsertion reaction of ions. The Li + The movement of ions between the two poles maintains the balance of charge and substance in the system.

[0003] In addition, an innovative type of battery that significantly improves the energy density of the above-mentioned LIBs is the fluoride ion (F - There is an anion-based fluoride-ion battery that utilizes the reaction of fluoride with metals to produce polyvalent metal fluorides and the reverse reaction (defluorination of metal fluorides). In this battery, the lightest halide ion, F, moves between the two electrodes. - ion (M=19), and optionally 2-3 or more F per metal atom. - The main factor that results in the high energy density described above is the participation of ions (and an equal number of electrons) in the electrode reaction.

[0004] The fluoride-ion battery does not require a host lattice, which is an essential component of LIBs. - This type of battery, in which ions play a key role in both the electrode reaction and the charge transfer in the electrolyte, is called FIB (Fluoride Ion Battery) or F - It is known by the abbreviation FSB (Fluoride Shuttle Battery), which emphasizes the role of bidirectional ion movement.

[0005] The reduction (defluorination) reaction of metal fluorides, one of the basic elements of fluoride-ion batteries, was reported in a number of studies in the 1970s, when solid electrolytes were attracting attention. However, it was only relatively recently that significant reversibility of charging and discharging, which is essentially essential for secondary batteries, was confirmed, albeit incompletely, within the framework of solid-state batteries.

[0006] Moreover, due to limitations generally associated with the ionic conductivity of solid electrolytes and the electrochemical reactivity at solid / solid interfaces, there have only been a few reports of room-temperature operation of solid-state FIB batteries published very recently.

[0007] In principle, the above restrictions are eliminated in wet batteries that use a non-aqueous electrolyte to transport fluoride ions. There is no shortage of prior patents and academic papers on electrolytes that can be used for this purpose. A representative example is a method using an ionic liquid that dissolves various fluoride salts relatively easily (Patent Document 1), and a method has also been reported in which a so-called anion receptor (anion acceptor) is added to a high-boiling point general-purpose organic solvent to promote the dissolution of fluoride. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2016-62821 A Summary of the Invention [Problem to be solved by the invention]

[0009] Here, in the above-mentioned Patent Document 1, as a negative electrode active material used in a fluoride ion battery, lF x However, according to the study by the present inventors, aluminum trifluoride (AlF 3 It was found that it was difficult to make the battery reaction proceed reversibly when using

[0010] Furthermore, the above-mentioned Patent Document 1 discloses that a material having electronic conductivity, such as various carbon materials, may be contained in the negative electrode active material as a conductive material (conductive assistant). However, according to the study by the present inventors, it was also found that when a conductive material (conductive assistant) made of a carbon material is contained in a negative electrode used in a fluoride ion battery, the original battery reaction cannot be sufficiently promoted.

[0011] Therefore, an object of the present invention is to provide a means for allowing the reversible battery reaction in a fluoride ion battery to proceed sufficiently. [Means for solving the problem]

[0012] In order to achieve the above object, the present inventors have conducted extensive research and have found that a reversible battery reaction can be sufficiently promoted by incorporating a metal fluoride, the defluorination reaction potential of which satisfies a predetermined relationship with the reductive decomposition potential of a passive film made of oxide and fluoride formed on the surface of a negative electrode current collector, into a negative electrode active material layer as a negative electrode active material, and by configuring the negative electrode current collector to be made of aluminum, magnesium, or an alloy thereof, and by configuring the negative electrode active material layer to not contain a conductive assistant made of a carbon material, thereby completing the present invention.

[0013] That is, according to one embodiment of the present invention, there is provided a negative electrode for a fluoride ion battery, comprising a negative electrode active material layer containing a negative electrode active material and a negative electrode current collector for collecting current from the negative electrode active material layer, wherein the negative electrode is characterized in that the negative electrode active material contains a metal fluoride, the defluorination reaction potential of the metal fluoride is higher than the reductive decomposition potential of a passivation film made of an oxide and a fluoride formed on the surface of the negative electrode current collector, the negative electrode current collector is made of aluminum, magnesium, or an alloy thereof, and the negative electrode active material layer does not contain a conductive assistant made of a carbon material. Effect of the Invention

[0014] According to the present invention, the use of a negative electrode active material having the above-mentioned predetermined defluorination reaction potential ensures the progress of a reversible battery reaction, and the use of a negative electrode current collector made of a specific constituent material and not using a conductive material (conductive assistant) made of a carbon material suppresses the progress of the reduction decomposition reaction of the electrolyte, thereby making it possible to sufficiently progress the reversible battery reaction. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a conceptual diagram showing the principle of a fluoride ion battery according to one embodiment of the present invention. [Diagram 2] 2(A) to (F) are cyclic voltammograms obtained as a result of cyclic voltammetry (CV) measurements of Reference Examples 1 to 6, respectively. [Diagram 3] 3(A) to (F) are chronopotentiograms obtained as a result of chronopotentiometry (CP) measurements of Reference Examples 1 to 6, respectively. [Figure 4] Figure 4 (A) and (B) are cyclic voltammograms obtained as a result of performing CV measurements on an aluminum (Al) foil alone and a magnesium (Mg) foil alone, respectively. [Diagram 5] 5(A) to 5(C) are cyclic voltammograms obtained as a result of cyclic voltammetry (CV) measurements of Example 1, Example 2, and Comparative Example 1, respectively. [Figure 6] FIG. 6 is a chronopotentiogram obtained as a result of the chronopotentiometry (CP) measurement in Example 2. [Figure 7] 7(A) to (C) are chronopotentiograms obtained as a result of chronopotentiometry (CP) measurements of Example 3, Comparative Example 2, and Comparative Example 3, respectively. [Figure 8] FIG. 8 (A) to (D) show charge / discharge curves for Comparative Example 4 and Examples 4-1 to 4-3, respectively. [Figure 9]9A and 9B show charge / discharge curves for Comparative Example 5 and Example 5, respectively. [Figure 10] FIG. 10 (A) to (C) show charge / discharge curves for Examples 6-1 to 6-3, respectively. [Figure 11] FIGS. 11A and 11B show charge / discharge curves for Example 7-1 and Example 7-2, respectively. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] According to one embodiment of the present invention, there is provided a negative electrode for a fluoride ion battery, the negative electrode having a negative electrode active material layer containing a negative electrode active material and a negative electrode current collector that collects current from the negative electrode active material layer, the negative electrode active material containing a metal fluoride, a defluorination reaction potential of the metal fluoride being higher than a reductive decomposition potential of a passive film made of an oxide and a fluoride that is formed on a surface of the negative electrode current collector, a constituent material of the negative electrode current collector being aluminum, magnesium, or an alloy thereof, and the negative electrode active material layer not containing a conductive assistant made of a carbon material.

[0017] Hereinafter, embodiments of a negative electrode for a fluoride ion battery and a fluoride ion battery according to the present invention will be described in detail with reference to the drawings.

[0018] FIG. 1 is a conceptual diagram showing the principle of a fluoride ion battery according to one embodiment of the present invention. As shown in FIG. 1, the fluoride ion battery 1 has a positive electrode 10, a negative electrode 20, and an electrolyte layer 30 arranged between the positive electrode 10 and the negative electrode 20. In the embodiment shown in FIG. 1, the positive electrode 10 has a configuration in which a positive electrode active material layer 12 is arranged on one surface of a positive electrode current collector made of aluminum (Al) foil 11. The positive electrode active material layer 12 is a composite layer containing a positive electrode active material 13 and a binder (not shown). In contrast, the negative electrode 20 has a configuration in which a negative electrode active material 21 is supported in the pores of foamed aluminum 22, which is a conductive porous structure (conductive porous body). Here, the foamed aluminum 22 on the negative electrode 20 side functions as a negative electrode current collector. The electrolyte layer 30 of this embodiment contains fluoride ions (F - An electrolytic solution (liquid electrolyte) containing . is used. The positive electrode current collector made of the aluminum (Al) foil 11 and the negative electrode current collector made of the foamed aluminum 22 are connected to an external load 40.

[0019] With this configuration, when the fluoride ion battery 1 is discharged, a voltage is applied to the external load 40 and a current flows. At this time, the fluoride ions (F - ) mediates the battery reaction by moving through the electrolyte layer 30 from the positive electrode 10 side to the negative electrode 20 side. On the other hand, when charging the fluoride ion battery 1, an external power source is connected to the positive electrode 10 and the negative electrode 20 instead of the external load 40, and fluoride ions (F - Charging is accomplished by forcing the

[0020] <Anode for fluoride ion batteries> The main components of the negative electrode for a fluoride ion battery according to the present embodiment will be described below. The negative electrode for a fluoride ion battery according to the present embodiment has a negative electrode active material layer containing a negative electrode active material, and a negative electrode current collector that collects current from the negative electrode active material layer.

[0021] [Negative electrode active material layer] The negative electrode active material layer includes a negative electrode active material. In the negative electrode according to this embodiment, the negative electrode active material includes a metal fluoride. The defluorination reaction potential of the metal fluoride is characterized in that it is a potential higher than the reductive decomposition potential of a passivation film made of an oxide and a fluoride formed on the surface of the negative electrode current collector. Here, the defluorination reaction potential of the metal fluoride included in the negative electrode active material is a value specific to the negative electrode active material. For example, TiF 3 , Al 0.97 Ti 0.03 F 3 and CeF 3 The defluorination reaction potentials of the negative electrode current collector and the negative electrode current collector are -1.95 [V vs. SHE (standard hydrogen electrode)], -2.10 [V vs. SHE], and -2.62 [V vs. SHE], respectively. Therefore, the configuration of the negative electrode current collector and the like may be determined so that these defluorination reaction potentials are higher than the reductive decomposition potential of the passivation film made of oxide and fluoride formed on the surface of the negative electrode current collector. Whether or not the negative electrode for a fluoride ion battery satisfies the above-mentioned predetermined relationship can be determined from a charge / discharge curve obtained by performing a charge / discharge test, as described in the Examples section below.

[0022] There is no particular restriction on the specific type of metal fluoride used as the negative electrode active material, as long as it satisfies the above-mentioned requirements with respect to the passive film formed on the surface of the negative electrode current collector. 1-x (Ti) x F 3 (where 0 <x≦0.5である)、Ti 1-y (Al) y F 3 (where 0≦y≦0.5) and CeF 3It is preferable to contain at least one selected from the group consisting of these. By satisfying the above provisions with the passive film formed on the surface of the negative electrode current collector, a reversible battery reaction can proceed sufficiently. Here, x is a real number greater than 0 and not more than 0.5, and there is no particular limitation, but it is preferably 0.01 or more and 0.1 or less, more preferably 0.02 or more and 0.5 or less. Also, y is a real number greater than or equal to 0 and not more than 0.5, and there is no particular limitation, but it is preferably 0.01 or more and 0.1 or less, more preferably 0.02 or more and 0.08 or less. Among them, from the viewpoint of being able to particularly configure a high-capacity fluoride ion battery, the metal fluoride is Al 1-x (Ti) x F 3 (where 0 < x ≤ 0.5) is more preferably included. Note that Al as the negative electrode active material 1-x (Ti) x F 3 and Ti 1-y (Al) y F 3 (y > 0) can be produced by weighing the powder of aluminum trifluoride (AlF 3 ) and the powder of titanium trifluoride (TiF 3 ) in a desired mass ratio under an inert atmosphere such as argon or nitrogen, and performing a mixing process using a mixing device such as a ball mill.

[0023] Note that the negative electrode active material layer may further contain a negative electrode active material other than the above-described negative electrode active material. However, from the viewpoint of sufficiently obtaining the effects of the present invention, the content of Al 1-x (Ti) x F 3 (0 < x ≤ 0.5), Ti 1-y (Al) y F 3 (0 ≤ y ≤ 0.5) or CeF 3 is preferably 50% by mass or more, more preferably 70% by mass or more, still more preferably 80% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, and most preferably 100% by mass.

[0024] The negative electrode active material layer according to this embodiment may further include a binder, such as polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), and polyimide (PI).

[0025] On the other hand, the negative electrode active material layer according to this embodiment is characterized in that it does not contain a conductive assistant made of a carbon material. This is because, as demonstrated in the Examples section described later, when the negative electrode active material layer contains a conductive assistant made of a carbon material, a side reaction due to reductive decomposition of the electrolyte proceeds, the battery reaction does not proceed sufficiently, and sufficient charge / discharge characteristics cannot be obtained. Note that the provision "does not contain a conductive assistant made of a carbon material" also includes cases where a trace amount of a conductive assistant made of a carbon material is added, for example, for the purpose of avoiding patent infringement. For example, the carbon material in the negative electrode active material layer Even when the blending amount of the conductive assistant made of a material is 3 mass % or less, the condition "conductive assistant made of a carbon material is not included" is satisfied. The negative electrode active material layer may contain a conductive assistant made of a material other than a carbon material (e.g., a metal, etc.), but it is preferable to contain as little of this as possible.

[0026] There are no particular limitations on the compounding ratio of each component contained in the negative electrode active material layer, but when the negative electrode active material layer contains a negative electrode active material and a binder, the compounding ratio of these components is preferably 70:30 to 99.5:0.5 (active material:binder (mass ratio)), and more preferably 90:10 to 99:1 (active material:binder (mass ratio)).

[0027] [Negative electrode current collector] The negative electrode current collector is a member that collects the current from the negative electrode active material layer. Therefore, the negative electrode current collector must be made of a conductive material. In the negative electrode according to this embodiment, the negative electrode current collector is characterized in that the material is aluminum (Al), magnesium (Mg), or an alloy thereof. This configuration has the advantage that the progress of side reactions due to the reduction and decomposition of the electrolyte can be significantly suppressed, as demonstrated in the Examples section described later. It is speculated that the mechanism by which such an effect is achieved is that the passive film is stable on the surface of the negative electrode current collector made of Al or Mg in the reaction potential region of the active material.

[0028] The shape of the negative electrode current collector is not particularly limited as long as it can hold the above-mentioned negative electrode active material (or a composite material containing the negative electrode active material and an additive such as a binder). Examples of the shape of the negative electrode current collector include a foil shape and a conductive porous structure (conductive porous body). The conductive porous body is a member having a porous structure (a large number of voids) inside and has conductivity, and here, a conductive porous body made of aluminum (Al) or magnesium (Mg) or an alloy thereof is exemplified. Preferably, the conductive porous body constituting the negative electrode current collector is made of foamed metal, and more preferably, it is made of foamed aluminum. As described above, one of the features of the negative electrode according to this embodiment is that it does not use a conductive assistant made of a carbon material (for example, carbon black such as acetylene black, graphite, carbon nanotubes, etc.), but by forming the negative electrode current collector using a conductive porous body made of foamed metal, it is possible to form a sufficiently good conductive path even in such a case.

[0029] Fluoride-ion battery According to another embodiment of the present invention, there is also provided a fluoride ion battery having a positive electrode, a negative electrode, and an electrolyte layer containing an electrolyte disposed between the positive electrode and the negative electrode, as shown in Fig. 1, in which the negative electrode is the negative electrode for a fluoride ion battery according to the embodiment of the present invention described above. The shape of the fluoride ion battery is not particularly limited, and examples thereof include a coin type, a button type, a sheet type, a laminated type, a cylindrical type, a flat type, and a square type. Below, components other than the negative electrode in the fluoride ion battery will be briefly described.

[0030] [Positive electrode current collector] The positive electrode current collector is a member that collects the current from the positive electrode active material layer. Therefore, the positive electrode current collector must be made of a conductive material. In the positive electrode according to this embodiment, the material of the positive electrode current collector is not particularly limited, but may be an aluminum (Al) foil as shown in FIG. 1, other metal current collectors used in conventionally known secondary batteries, or a resin current collector having a conductive resin layer.

[0031] [Cathode active material layer] The positive electrode active material layer contains a positive electrode active material. Positive electrode active materials that can be used in the positive electrode according to the present embodiment include pure metals, alloys, metal oxides, and metal fluorides. Examples of the elements that can be used include one or more of Ag, Pt, Au, Cr, Mo, W, V, Fe, Co, Ni, Cu, Zn, S, Sb, Bi, Sn, Pb, and C. Of these, the positive electrode active material preferably contains any of the elements Fe, Co, Ni, Cu, Pb, Bi, and Zn. In particular, the positive electrode active material more preferably contains Cu, such as Cu metal, Cu alloy, and Cu fluoride.

[0032] The positive electrode active material layer constituting the positive electrode according to the present embodiment may further contain a binder and a conductive assistant as described in the section on the negative electrode active material layer.

[0033] [Electrolyte layer] The electrolyte layer is a member disposed between the positive electrode (positive electrode active material layer) and the negative electrode (negative electrode active material layer), and contains fluoride ions (F - ) can pass through the electrolyte layer. In the fluoride ion battery according to the present embodiment, the electrolyte contained in the electrolyte layer is usually a liquid electrolyte (electrolytic solution). When the electrolyte layer is a liquid electrolyte (electrolytic solution), a separator may be used in the electrolyte layer. The separator is not particularly limited as long as it has a composition that can withstand the range of use of the fluoride ion battery, and examples of the separator include polymer nonwoven fabrics such as polypropylene nonwoven fabrics, polyphenylene sulfide nonwoven fabrics, and aramid nonwoven fabrics, and microporous films of olefin resins such as polyethylene and polypropylene. These may be used alone or in combination.

[0034] As the liquid electrolyte (electrolytic solution), a conventionally known electrolytic solution for fluoride ion batteries may be used, but it is particularly preferable to use an organic electrolytic solution containing a single or mixed organic solvent of an ester or lactone having an α-position hydrogen (e.g., γ-butyrolactone, ε-caprolactone, etc.) and an alkali metal fluoride having an alkali metal cation and a fluoride ion (e.g., cesium fluoride, etc.). By using such an electrolytic solution as the electrolyte, excellent capacity characteristics can be exhibited.

[0035] [Alkali metal fluorides] Ionically conductive fluoride ions that directly participate in the electrode reaction can also be introduced into the electrolyte by dissolving organic fluorides, but this is not suitable for high-capacity fluoride-ion batteries due to issues such as the electrochemical stability of the coexisting organic cations. Considering the effect on the weight energy density of secondary batteries as another condition, the most desirable source of fluoride ions is an alkali metal fluoride such as lithium fluoride (LiF), sodium fluoride (NaF), potassium fluoride (KF), rubidium fluoride (RbF), or cesium fluoride (CsF).

[0036] [Mixed lithium salts] The fluoride ion conductive electrolyte in which only alkali metal fluorides are dissociated and dissolved at a concentration of 1 mM or more is prone to side reduction reactions involving the solvent derived from fluoride ions in the negative high potential region, which competes with the fluorination reaction of metals less noble than zinc and hinders the original operation of the battery. This problem can be easily solved by mixing an excess of any lithium salt that can be co-dissolved in the electrolyte of this embodiment, such as LiFSA (FSA: bis(fluorosulfonyl)amide), into the electrolyte, making it possible to operate a battery that utilizes the fluorination reaction of the most noble metal species, such as aluminum or lanthanum.

[0037] In preparing the mixed electrolyte solution, it is desirable to prepare the concentration of the lithium salt added in excess to be at least 3 times, preferably 5 times, and more preferably about 10 times, the concentration of the dissociated alkali metal fluoride. If the concentration (amount added) of this lithium salt is 3 times or more, it is desirable because the fluoride ion and lithium ion do not form an insoluble solid matter, and therefore the fluoride ion concentration is not reduced.

[0038] The anion species of the lithium salt is FSA - Besides TFSA - , B.E.T.A. - , B.F. 4 - , P.F. 6 - , ClO 4 - In other words, the lithium salt to be added in excess is LiFSA, LiTFSA, LiBETA, LiBF 4 , LiPF 6 , LiClO 4 It is preferred that the compound is any one of the above or a mixture of two or more thereof.

[0039] [Mixed barium salts] Although it is not as effective as lithium salts, Ba(FSA) 2The irreversible reduction current in the high negative potential region can also be suppressed by mixing an excess of a barium salt, such as fluoride, into the electrolyte. In preparing the above mixed electrolyte, it is desirable to prepare the concentration of the excess barium salt to be at least 3 times, preferably 5 times, and more preferably about 10 times, the concentration of the dissociated alkali metal fluoride. If the concentration (amount added) of this barium salt is 3 times or more, it is desirable because the fluoride ion and barium ion do not form an insoluble solid matter, and therefore the fluoride ion concentration is not reduced. As the anion species of the barium salt, FSA - Besides TFSA - , B.E.T.A. - , B.F. 4 - That is, the barium salt added in excess is Ba(FSA). 2 , Ba(TFSA) 2 , Ba(BETA) 2 , Ba(BF 4 ) 2 It is preferred that the compound is any one of the above or a mixture of two or more thereof.

[0040] [Boron-containing compounds] In the fluoride ion battery according to the present embodiment, the electrolyte (electrolytic solution) can realize a higher reversible capacity by including a compound containing boron as an additive. There is no particular limitation on the type of the compound containing boron, and examples of the compound include conventionally known boron compounds, among which a compound having one boroxine structure (monocyclic boroxine compound) is preferable. "Boroxine" refers to a compound having a structure of B 3 H 3 O 3It is a heterocyclic compound represented by the chemical formula: and has a six-membered ring structure in which boron atoms bonded to one hydrogen atom and oxygen atoms are arranged alternately. Examples of monocyclic boroxine compounds having one boroxine structure include 2,4,6-trimethoxyboroxine (TMBx), 2,4,6-triphenylboroxine (TPBx), 2,4,6-tris(4-fluorophenyl)boroxine (TFPBx) and 2,4,6-tris(m-terphenyl-5'-yl)boroxine (TTBx). In addition, the monocyclic boroxine compounds disclosed in International Publication WO 2017 / 082268 may be used.

[0041] When the electrolyte (electrolytic solution) contains a compound containing boron, its concentration is not particularly limited, but from the viewpoint of obtaining a high reversible capacity, it is preferably 0.8 M or less, more preferably 0.5 M or less, even more preferably 0.05 to 0.5 M, particularly preferably 0.05 to 0.3 M, and most preferably 0.05 to 0.1 M. EXAMPLES

[0042] The present invention will be explained more specifically below with reference to experimental examples.

[0043] [Reference example 1] A commercially available current collector made of aluminum (Al) foil (thickness 20 μm) was cut to a size of 5 mm × 10 mm, and the metal surface other than the reaction surface was masked by heat fusion with a polypropylene (PP) seal film so that the reaction surface was 5 mm × 5 mm in size, leaving a portion of the terminal connection section, to produce the electrode of this reference example.

[0044] [Reference example 2] An electrode of this reference example was produced in the same manner as in the above-mentioned Reference Example 1, except that a commercially available magnesium (Mg) foil was used as a current collector instead of an aluminum (Al) foil.

[0045] [Reference example 3] An electrode of this reference example was produced in the same manner as in the above-mentioned Reference Example 1, except that a commercially available copper (Cu) foil was used as a current collector instead of an aluminum (Al) foil.

[0046] [Reference example 4] An electrode of this reference example was produced in the same manner as in the above-mentioned Reference Example 1, except that a commercially available nickel (Ni) foil was used as the current collector instead of the aluminum (Al) foil.

[0047] [Reference example 5] A conductive assistant made of acetylene black (AB) which is a carbon material and polyvinylidene fluoride (PVdF) which is a binder were kneaded in a mass ratio of 50:50, and N-methyl-2-pyrrolidone (NMP) was further added to make a slurry with an appropriate viscosity. The obtained slurry was applied to one surface of a current collector made of aluminum (Al) foil similar to that in Reference Example 1, and vacuum dried at 120°C. Next, a pressing process was performed so that the porosity was 40 to 50%, to prepare an electrode sheet. The obtained electrode sheet was cut to a size of 5 mm x 10 mm, and a part of the composite surface was peeled off so that the composite surface had a size of 5 mm x 5 mm, to prepare the electrode of this Reference Example.

[0048] [Reference example 6] The electrode of this reference example was produced in the same manner as in Reference Example 5 described above, except that carbon nanotubes (CNTs), which are also carbon materials, were used as the conductive assistant instead of acetylene black (AB).

[0049] [Evaluation of electrolyte reduction resistance] The electrodes prepared in each of the above-mentioned Reference Examples 1 to 6 were evaluated for their resistance to reduction in the electrolyte.

[0050] Specifically, first, a beaker cell was prepared using the electrodes prepared in each of the above reference examples as the working electrode, an electrode sheet (activated carbon: PTFE = 70: 30 (mass ratio)) consisting of activated carbon and a binder polytetrafluoroethylene (PTFE) as the counter electrode, and an Ag wire as the reference electrode. Here, the electrolyte used was a solution of LiFSA (0.5 mol / L) and CsF (0.038 mol / L) dissolved in γ-butyrolactone (GBL) (see JP 2021-36512 A).

[0051] Using each of the beaker cells prepared above, the reduction resistance of the electrolyte was evaluated by cyclic voltammetry (CV) measurement and chronopotentiometry (CP) measurement.

[0052] Cyclic voltammetry (CV) measurements were performed in an argon atmosphere at room temperature, with a sweep rate of 1 mV / sec. Cyclic voltammograms obtained as a result of the cyclic voltammetry (CV) measurements of Reference Examples 1 to 6 are shown in (A) to (F) of FIG. 2, respectively. In addition, the Al / AlF 3 The reduction decomposition current value of the electrolyte was compared up to about -2.4 V (vs. Ag), which is the fluorination / defluorination reaction potential of the electrolyte. 2 The value below is 0.1mA / cm 2 Those that are over are marked with an × (NG) and are shown in Table 1 below.

[0053] The chronopotentiometry (CP) measurements were performed in an argon atmosphere at room temperature, and the current rate of the constant current test was 10 μA. The chronopotentiograms obtained as a result of the chronopotentiometry (CP) measurements of Reference Examples 1 to 6 are shown in (A) to (F) of FIG. 3, respectively. Based on each chronopotentiogram, a reaction plateau at which the potential was constant was observed, and the potential was determined to be Al / AlF 3The potentials that are more noble than the fluorination / defluorination reaction potential of -2.4 V (vs. Ag) are indicated as ◯ (OK), and the potentials that are more noble than that are indicated as × (NG) in Table 1 below. And Reference Example 2 was ◯ (OK).

[0054] [Table 1]

[0055] As can be seen from the results shown in Figs. 2(A) and 3(A) and Figs. 2(B) and 3(B), in Reference Examples 1 and 2, the side reaction due to the reductive decomposition of the electrolyte was Al / AlF 3 The reaction does not proceed unless the potential is lower than the reaction potential. Therefore, in the negative electrode of a fluoride ion battery using these materials as a current collector, it is considered that the defluorination reaction of the negative electrode active material proceeds preferentially over the side reaction due to the reductive decomposition of the electrolyte during charging of the fluoride ion battery.

[0056] In contrast, as can be seen from the results shown in Figures 2(C) and 3(C) and Figures 2(D) and 3(D), a side reaction thought to be reductive decomposition of the electrolyte was observed around -0.6 V (vs. standard hydrogen electrode (SHE)) in Reference Examples 3 and 4. Therefore, in the negative electrodes for fluoride ion batteries using these materials as current collectors, it is considered that the side reaction due to reductive decomposition of the electrolyte proceeds preferentially over the defluorination reaction from the negative electrode active material during charging of the fluoride ion battery.

[0057] Furthermore, as can be seen from the results shown in Figures 2(E) and 3(E) and Figures 2(F) and 3(F), in Reference Examples 5 and 6, which used a conductive assistant made of a carbon material, a side reaction thought to be reductive decomposition of the electrolyte was observed around -1.0 V (vs. SHE). Thus, on the surface of the conductive assistant made of a carbon material, Al / AlF 3 It is believed that the reductive decomposition of the electrolyte occurs at a potential more noble than the reaction potential, and therefore the defluorination reaction of the negative electrode active material, which is the original electrode reaction, is inhibited.

[0058] [Example 1] (Synthesis of active materials) Commercially available AlF 3 Powder (FUJIFILM Wako Pure Chemical Corporation) with commercially available TiF as an additive 3 The mixture was mixed in a ball mill under an argon atmosphere to obtain the active material of this example, Al powder (Sigma-Aldrich). 0.97 Ti 0.03 F 3 was synthesized.

[0059] (Preparation of electrodes) The active material (Al) prepared above was applied to one surface of a commercially available current collector made of aluminum (Al) foil. 0.97 Ti 0.03 F 3 ) was crimped to prepare the electrode of this example.

[0060] (Cell Preparation) The electrode prepared above was used as the working electrode, and an electrode sheet consisting of activated carbon and polytetrafluoroethylene (PTFE) as a binder (activated carbon: PTFE = 70: 30 (mass ratio)) was A beaker cell of this example was fabricated using a counter electrode and a Ag wire as a reference electrode. The electrolyte used was a solution of LiFSA (0.14 mol / L) and CsF (0.012 mol / L) dissolved in γ-butyrolactone (GBL).

[0061] [Example 2] The beaker cell of this example was produced in the same manner as in Example 1 above, except that a commercially available magnesium (Mg) foil was used as the current collector instead of the aluminum (Al) foil.

[0062] [Comparative Example 1] Al 0.97 Ti 0.03 F 3 Instead, TiF 3 AlF not mixed 3A beaker cell of this comparative example was produced in the same manner as in Example 1 above, except that a powder was used as the active material.

[0063] [Evaluation of the reactivity of active materials] We evaluated the reactivity of the active material in the beaker cells prepared in each of the above-mentioned Example 1, Example 2, and Comparative Example 1. Specifically, we evaluated the reduction resistance of the electrolyte by cyclic voltammetry (CV) measurement and chronopotentiometry (CP) measurement using the beaker cells prepared in each of the above-mentioned experimental examples.

[0064] The cyclic voltammetry (CV) measurement was performed in an argon atmosphere at room temperature, with a sweep rate of 20 mV / sec. Here, in order to confirm the degree of progress of the redox reaction in the electrolyte on the surfaces of the aluminum (Al) foil and magnesium (Mg) foil, which are the current collectors, the cyclic voltammograms obtained as a result of the CV measurement of the aluminum (Al) foil alone and the magnesium (Mg) foil alone are shown in (A) and (B) of FIG. 4. Meanwhile, the cyclic voltammograms obtained as a result of the cyclic voltammetry (CV) measurement of Example 1, Example 2, and Comparative Example 1 are shown in (A) to (C) of FIG. 5, respectively. Based on each cyclic voltammogram, the Al / AlF 3 The magnitudes of the reduction current peak and the oxidation current peak were compared around -2.4 V (vs. Ag), which is the fluorination / defluorination reaction potential of the fluorine-defluorination reaction, to determine the fluorination / defluorination reaction activity. As a result, those judged to have sufficient reversible reaction activity were marked with ◯ (OK), and those judged to have insufficient reversible reaction activity were marked with × (NG), as shown in Table 2 below. As shown in Table 2, Example 1 and Example 2 were ◯ (OK).

[0065] Chronopotentiometry (CP) measurements were also performed for Example 2. Specifically, the CP measurements were performed in an argon atmosphere at room temperature, and the current rate for the constant current test was 0.25 mA / cm. 2The chronopotentiogram obtained as a result of the CP measurement in Example 2 is shown in FIG.

[0066] [Table 2]

[0067] As can be seen from a comparison between FIG. 4(A) and FIG. 5(A), the aluminum current collector Aluminum (Al) foil is applied to the surface as an active material. 0.97 Ti 0.03 F 3 Similarly, as can be seen from the comparison of Fig. 4(B) and Fig. 5(B), the surface of the magnesium (Mg) foil current collector is supported with Al as an active material, and the reversible redox reaction proceeds. 0.97 Ti 0.03 F 3 By supporting Mg foil, the reduction side reaction that occurs when Mg foil is used alone is strongly suppressed, and a reversible oxidation-reduction reaction proceeds. This is also supported by the chronopotentiogram for Example 2 shown in FIG. 6. From these facts, it can be said that the negative electrode for a fluoride ion battery according to the present invention is a promising candidate for improving the battery performance of a fluoride ion battery. The cyclic voltammogram for Comparative Example 1 shown in FIG. 5(C) did not confirm the progress of a reversible oxidation-reduction reaction. This is because AlF, which is a highly insulating active material, 3 This is believed to be because the progress of the oxidation-reduction reaction on the surface of the aluminum (Al) foil was inhibited by the support of the metal on the surface of the Al foil, which is the current collector.

[0068] [Example 3] (Synthesis of active materials) Commercially available AlF 3 Additives to powders include TiF 3 In a predetermined ratio, the mixture was mixed in a ball mill under an argon atmosphere to obtain the active material Al 0.97 Ti 0.03 F 3 was synthesized.

[0069] (Preparation of electrodes) The active material prepared above and polyvinylidene fluoride (PVdF) as a binder were mixed in a mass ratio of 95:5, and N-methyl-2-pyrrolidone (NMP) was further added to prepare a slurry with an appropriate viscosity. The obtained slurry was filled into a conductive porous aluminum foam (Aluminum Celmet, manufactured by Sumitomo Electric Industries, Ltd., porosity 96%), and after drying, the mixture was pressed to prepare the electrode of this example.

[0070] (Cell Preparation) The beaker cell of this example was fabricated using the electrode fabricated above as the working electrode, an electrode sheet (activated carbon: PTFE = 70: 30 (mass ratio)) made of activated carbon and a binder polytetrafluoroethylene (PTFE) as the counter electrode, and an Ag wire as the reference electrode. The electrolyte used was a solution of LiFSA (0.14 mol / L) and CsF (0.012 mol / L) dissolved in γ-butyrolactone (GBL).

[0071] [Comparative Example 2] The active material prepared in the above-mentioned Example 3, acetylene black (AB) as a conductive assistant made of a carbon material, and polyvinylidene fluoride (PVdF) as a binder were kneaded in a mass ratio of 75:12.5:12.5, and N-methyl-2-pyrrolidone (NMP) was further added to make a slurry with an appropriate viscosity. The obtained slurry was applied to one surface of a copper (Cu) foil (thickness 20 μm) as a current collector, and after drying, a pressing process was performed to prepare an electrode of this comparative example. Then, a beaker cell of this comparative example was prepared by the same method as that of the above-mentioned Example 3, except that this electrode was used.

[0072] [Comparative Example 3] A beaker cell of this comparative example was produced in the same manner as in Comparative Example 2 described above, except that an aluminum (Al) foil was used as the current collector instead of the copper (Cu) foil.

[0073] [Evaluation of charge / discharge characteristics] The charge / discharge characteristics were evaluated in the beaker cells prepared in each of the above-mentioned Example 3, Comparative Example 2, and Comparative Example 3. Specifically, the charge / discharge characteristics of each cell was evaluated by chronopotentiometry (CP) measurement using the beaker cells prepared in each of the above-mentioned experimental examples.

[0074] The chronopotentiometry (CP) measurement was performed in an argon atmosphere at room temperature, and the current rate of the constant current test was equivalent to 0.04 C. The chronopotentiograms obtained as a result of the chronopotentiometry (CP) measurement of Example 3, Comparative Example 2, and Comparative Example 3 are shown in (A) to (C) of FIG. 7, respectively. In addition, based on each chronopotentiogram, it was evaluated whether a reversible charge / discharge reaction by fluorination / defluorination of the active material was progressing, and whether sufficient cycle characteristics were achieved. Those that were not problematic in practical use were marked as ◯ (OK), and those that were not were marked as × (NG), as shown in Table 3 below. As shown in Table 3, only Example 3 was ◯ (OK).

[0075] [Table 3]

[0076] Here, as shown in FIG. 7(A), in Example 3, Al / AlF 3 Since the plateau potential of the charge-discharge reaction was confirmed near -2.4 V (vs. Ag), which is the fluorination-defluorination reaction potential of the active material, it is considered that a reversible charge-discharge reaction due to fluorination-defluorination of the active material is proceeding. In addition, as shown in Figure 7(A), the cycle characteristics of Example 3 were also good.

[0077] On the other hand, in Comparative Example 2 shown in FIG. 7(B), no reversible charge / discharge capacity was obtained. This is believed to be due to the use of AB, a conductive assistant made of a carbon material, and the use of copper (Cu) foil as the current collector, which caused the reductive decomposition reaction of the electrolyte to proceed preferentially. In Comparative Example 3 shown in FIG. 7(C), the irreversible charge / discharge capacity was large, and the capacity deterioration due to the charge / discharge cycle was also large. This is believed to be due to the use of the conductive assistant (AB), also made of a carbon material, which caused the reductive decomposition reaction of the electrolyte to proceed preferentially, despite the use of aluminum (Al) foil as the current collector.

[0078] [Comparative Example 4] (Preparation of electrodes) Commercially available TiF 3 A conductive additive (AB: acetylene black) was added to the powder in a mass ratio of 90:10, and the mixture was mixed in a ball mill under an argon atmosphere to obtain TiF 3 AB and PVdF were further added to the obtained mixture to obtain TiF 3 The mass ratio of AB:PVdF was adjusted to 75:12.5:12.5, and then NMP was added and kneaded to obtain a slurry with an appropriate viscosity. The obtained slurry was applied onto an Al foil, vacuum dried at 120°C, and pressed to obtain an electrode sheet with a porosity of 40 to 50%. The obtained electrode sheet was cut to 5 mm x 10 mm, and a part of the composite surface was peeled off so that the composite surface was 5 mm x 5 mm, to produce the electrode of this comparative example.

[0079] (Cell Preparation) A beaker cell of this comparative example was fabricated using the electrode fabricated above as the working electrode, an electrode sheet made of activated carbon and PTFE (activated carbon:PTFE=70:30 (mass ratio)) as the counter electrode, and an Ag wire as the reference electrode. The electrolyte used was a solution of LiFSA (0.14 mol / L) and CsF (0.012 mol / L) dissolved in GBL.

[0080] [Example 4-1] The same active material (TiF) as in Comparative Example 4 was applied to one surface of a commercially available current collector made of magnesium (Mg) foil.3 ) was compressed to prepare an electrode of this example. A beaker cell of this example was then prepared in the same manner as in Comparative Example 4, except that this electrode was used.

[0081] [Example 4-2] The same active material as in Comparative Example 4 (TiF 3 ) and PVdF were kneaded in a mass ratio of 95:5, and NMP was further added to obtain a slurry with an appropriate viscosity. The obtained slurry was filled into a conductive porous aluminum foam (porosity 96%), dried, and pressed to produce the electrode of this example. Then, a beaker cell of this example was produced by the same method as in Comparative Example 4 described above, except that this electrode was used.

[0082] [Example 4-3] (Synthesis of active materials) Commercially available TiF 3 AlF as an additive to the powder 3 In a predetermined ratio, the mixture was mixed in a ball mill under an argon atmosphere to obtain the active material of this embodiment, Ti 0.95 Al 0.05 F 3 The electrode and beaker cell of this example were produced in the same manner as in Example 4-2, except that this active material was used.

[0083] [Evaluation of charge / discharge characteristics] The charge / discharge characteristics of the beaker cells prepared in each of the above-mentioned Comparative Example 4 and Examples 4-1 to 4-3 were evaluated. Specifically, a charge / discharge test was performed on each beaker cell prepared in each of the above-mentioned experimental examples by a constant current test (charge / discharge rate: 0.02C) at room temperature (25°C), and the reversible capacity was measured in three cycles. The results are shown in Table 4 below. In addition, in each of the beaker cells prepared in the above-mentioned Examples 4-1 to 4-3, it was confirmed from the reaction potential and charge / discharge curves of each negative electrode active material that the defluorination reaction potential of the negative electrode active material was higher than the reductive decomposition potential of the passivation film made of oxides and fluorides formed on the surface of the negative electrode current collector.

[0084] [Table 4]

[0085] Here, the charge / discharge curves for the beaker cells produced in each of the above experimental examples are shown in Fig. 8 (A) to (D). As can be seen from these results, in Comparative Example 4, in which the negative electrode active material layer contains AB, a sufficient reversible capacity could not be obtained. In contrast, in each of the Examples, a sufficient reversible capacity could be obtained. Moreover, in Examples 4-2 and 4-3, in which foamed aluminum was used as the negative electrode current collector, a higher reversible capacity could be obtained, and furthermore, in which TiF was used as the negative electrode active material, 3 In Example 4-3, in which a small amount of Al was added to the electrolyte, particularly excellent charge / discharge characteristics were achieved.

[0086] [Comparative Example 5] As the negative electrode active material, TiF 3 Instead of powder, commercially available CeF 3 The electrode and beaker cell of this comparative example were produced in the same manner as in Comparative Example 4 above, except that a powder (Sigma-Aldrich) was used and Mg foil was used as the negative electrode current collector instead of Al foil.

[0087] [Example 5] As the negative electrode active material, TiF 3 Instead of the powder, the same active material as in Comparative Example 5 (CeF 3 The electrodes and beaker cell of this example were produced in the same manner as in Example 4-1 described above, except that the above-mentioned 1-hydroxyethyl ether was used.

[0088] [Evaluation of charge / discharge characteristics] The charge / discharge characteristics of the beaker cells prepared in each of the above-mentioned Comparative Example 5 and Example 5 were evaluated. Specifically, a charge / discharge test was performed on each beaker cell prepared in each of the above-mentioned experimental examples by a constant current test (charge / discharge rate: 0.02C) at room temperature (25°C), and the reversible capacity in one cycle was measured. The results are shown in Table 5 below. In the beaker cell prepared in the above-mentioned Example 5, it was confirmed from the reaction potential and charge / discharge curve of the negative electrode active material that the defluorination reaction potential of the negative electrode active material was higher than the reductive decomposition potential of the passivation film made of oxides and fluorides formed on the surface of the negative electrode current collector.

[0089] [Table 5]

[0090] Here, the charge / discharge curves for the beaker cells prepared in the above experimental examples are shown in FIG. 9 (A) (Comparative Example 5) and (B) (Example 5). As can be seen from these results, in Comparative Example 5, in which the negative electrode active material layer contains AB, only side reactions proceeded, and sufficient reversible capacity could not be obtained. In contrast, in Example 5, 3 The fluorination / defluorination reaction proceeded, and sufficient reversible capacity was obtained.

[0091] [Example 6-1] The beaker cell produced in Example 4-3 described above was used as the beaker cell of this example.

[0092] [Example 6-2] The beaker cell of this example was produced in the same manner as in Example 6-1 described above, except that 2,4,6-trimethoxyboroxine (TMBx), a type of boroxine compound, was added to the electrolyte at a concentration of 0.05 M.

[0093] [Example 6-3] The beaker cell of this example was produced in the same manner as in Example 6-2 described above, except that the concentration of TMBx added was 0.1M.

[0094] [Example 6-4] The beaker cell of this example was produced in the same manner as in Example 6-2 described above, except that the concentration of TMBx added was 0.5M.

[0095] [Evaluation of charge / discharge characteristics] The charge / discharge characteristics of the beaker cells prepared in each of the above-mentioned Examples 6-1 to 6-4 were evaluated. Specifically, a charge / discharge test was performed on each beaker cell prepared in each of the above-mentioned Examples by a constant current test (charge / discharge rate: 0.02C) at room temperature (25°C), and the reversible capacity was measured after three cycles. The results are shown in Table 6 below.

[0096] [Table 6]

[0097] Here, the charge / discharge curves for the beaker cells prepared in the above Examples 6-2 to 6-4 are shown in (A) to (C) of FIG. 10. As can be seen from these results, the addition of the boroxine compound improved the charge / discharge characteristics. This is believed to be because the addition of the boroxine compound forms a fluoride ion conductive coating on the surface of the negative electrode active material layer, thereby suppressing the progress of irreversible reactions such as the reductive decomposition of the electrolyte on the surface. In addition, in Examples 6-2 and 6-3, in which the concentration of the boroxine compound added was within the range of 0.05 to 0.1 M, particularly excellent charge / discharge characteristics were achieved.

[0098] [Example 7-1] The beaker cell produced in the above-mentioned Example 3 was used as the beaker cell of this example.

[0099] [Example 7-2] The beaker cell of this example was produced in the same manner as in Example 7-1 described above, except that 2,4,6-trimethoxyboroxine (TMBx), a type of boroxine compound, was added to the electrolyte at a concentration of 0.1 M.

[0100] [Evaluation of charge / discharge characteristics] The charge / discharge characteristics of the beaker cells prepared in each of the above-mentioned Examples 7-1 and 7-2 were evaluated. Specifically, a charge / discharge test was performed on each beaker cell prepared in each of the above-mentioned Examples by a constant current test (charge / discharge rate: 0.04C) at room temperature (25°C), and the reversible capacity was measured after three cycles. The results are shown in Table 7 below.

[0101] [Table 7]

[0102] Here, the charge-discharge curves for the beaker cells prepared in the above Examples 7-1 and 7-2 are shown in (A) and (B) of FIG. 11. As can be seen from these results, Al(Ti)F 3 As a negative electrode active material, the charge-discharge characteristics were improved by adding a boroxine compound. [Explanation of symbols]

[0103] 1 fluoride ion battery, 10 positive electrode, 11 Aluminum (Al) foil (positive electrode current collector), 12 positive electrode active material layer, 13 Positive electrode active material, 20 negative electrode, 21 negative electrode active material, 22 Foamed aluminum (negative electrode current collector), 30 electrolyte layer, 40 External load, F - Fluoride ion.

Claims

1. a negative electrode active material layer containing a negative electrode active material; a negative electrode current collector that collects current from the negative electrode active material layer; A negative electrode for a fluoride ion battery comprising: the negative electrode active material contains a metal fluoride, and a defluorination reaction potential of the metal fluoride is higher than a reductive decomposition potential of a passive film made of an oxide and a fluoride that is formed on a surface of the negative electrode current collector; the negative electrode current collector is made of aluminum, magnesium, or an alloy thereof; The negative electrode for a fluoride ion battery, wherein the negative electrode active material layer does not contain a conductive assistant made of a carbon material. 。

2. The metal fluoride is Al 1-x (Ti) x F 3 (where 0<x≦0.5), Ti 1-y (Al) y F 3 (where 0≦y≦0.5) and CeF 3 The negative electrode for a fluoride ion battery according to claim 1 , comprising at least one selected from the group consisting of:

3. The metal fluoride is Al 1-x (Ti) x F 3 3. The negative electrode for a fluoride ion battery of claim 2 comprising: wherein 0<x≦0.

5.

4. The negative electrode for a fluoride ion battery according to any one of claims 1 to 3, wherein the negative electrode current collector is made of a conductive porous body having pores, and the negative electrode active material is supported in the pores.

5. 5. The negative electrode for a fluoride ion battery according to claim 4, wherein the conductive porous body constituting the negative electrode current collector is made of foamed aluminum.

6. A positive electrode and A negative electrode; an electrolyte layer disposed between the positive electrode and the negative electrode and including an electrolyte; A fluoride ion battery having: The negative electrode is the negative electrode for a fluoride ion battery according to any one of claims 1 to 5.

7. 7. The fluoride ion battery according to claim 6, wherein the electrolyte is an organic electrolyte solution containing an ester-based or lactone-based single or mixed organic solvent having an α-position hydrogen, and an alkali metal fluoride having an alkali metal cation and a fluoride ion.

8. 8. The fluoride ion battery according to claim 6 or 7, wherein the electrolyte contains a compound containing boron as an additive.

9. 9. The fluoride ion battery of claim 8, wherein the compound containing boron includes a compound having one boroxine structure.

10. 10. The fluoride ion battery according to claim 8 or 9, wherein the concentration of the boron-containing compound in the electrolyte is 0.5 M or less.

Citation Information

Patent Citations

  • Electrolytic solution for fluoride ion batteries and fluoride ion battery

    JP2016062821A

  • Secondary battery

    JP2017010865A

  • Negative electrode current collector, and fluoride ion battery

    JP2017054721A

  • Method for producing negative electrode current collector for fluoride ion battery

    JP2017062987A

  • Negative electrode layer for fluoride ion battery and fluoride ion battery

    JP2017216209A